KEMAMPUAN SPASIAL MATEMATIS SISWA PADA MATERI GEOMETRI DITINJAU DARI MINAT BELAJAR SISWA - Andela, Sinta; Wahyuni, Rika; Husna, Nurul (Universitas Islam Sumatera Utara, 2024)
The purpose of this study was to describe students' mathematical spatial abilities in geometry material viewed from their learning interests. This research method is a qualitative study. The subjects of the study were students of class IX-B MTS Al-Fatah Singkawang. Data collection techniques in this study were based on learning interest questionnaires, mathematical spatial ability tests and interviews. The data analysis technique used was the Miles and Huberman model, namely data reduction, data presentation, data analysis, and drawing conclusions. The results showed that 1) students' mathematical spatial abilities in geometry material viewed from high learning interests had an average of 56.25 which was in the sufficient category. 2) students' mathematical spatial abilities in geometry material averaged 67.5 which was in the sufficient category. 3) students' mathematical spatial abilities viewed from low student learning interests had an average of 37.5 which was in the sufficient category.